2016
DOI: 10.1177/0194599815626147
|View full text |Cite
|
Sign up to set email alerts
|

Educational Value of a Medical Student–Led Head and Neck Cancer Screening Event

Abstract: Volunteer participation in a HNC screening program improves medical students' knowledge of HNC risk factors and symptoms. This innovative approach to students' education via participation and organization of screening events is a useful method of improving their HNC knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Recent studies in America showed poor baseline knowledge among medical students, with only 18 to 59% and 44 to 67% correctly identifying alcohol consumption and tobacco as risk factors for oral cancer. Less than a quarter (24%) of the medical students correctly identified HPV as a potential risk factor [27, 34]. The results from the Dutch dental students did not corroborate this knowledge deficit: 100, 88, and 64% named tobacco, alcohol, and HPV as risk factors for oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies in America showed poor baseline knowledge among medical students, with only 18 to 59% and 44 to 67% correctly identifying alcohol consumption and tobacco as risk factors for oral cancer. Less than a quarter (24%) of the medical students correctly identified HPV as a potential risk factor [27, 34]. The results from the Dutch dental students did not corroborate this knowledge deficit: 100, 88, and 64% named tobacco, alcohol, and HPV as risk factors for oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In America, 66% of medical schools do not include screening for head and neck cancer in their curricula. Even when students learn to perform this screening, the quality of this teaching is inconsistent [27]. It is likely that this contributes to the fact that 47% of medical students in America reported feeling ‘not very confident’ or less in examining the oral cavity for oral cancer [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was especially true in studentled outpatient clinics, with individuals reporting improved clinical skills, long term knowledge retention, and improved interest in pursuing oncology. 48,49 No compromise in patient care was reported in these cases. 50 This was not seen with simple observation of similar experiences or with non-repetitive and short term practice.…”
mentioning
confidence: 80%